2021
DOI: 10.1021/acs.jpcb.0c09156
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Dielectric Constant of Nanoconfined Water between Graphene Layers in the Presence of Salt

Abstract: Ultra-low dielectric constant of nanoconfined water between two flat slabs is a subject of recent experimental and theoretical research. The impact of dissolution of sodium chloride (NaCl) with various concentrations on the dielectric properties of nanoconfined water between graphene layers are investigated using molecular dynamics simulations. We found that, with increasing salt concentration, (i) the out-of-plane dielectric constant increases and (ii) the in-plane dielectric constant decreases non-linearly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Transport selectivity is usually based on size exclusion, and hence nanopore geometry and dimensions, , but also on molecular recognition via cognate receptors present inside the pore. Transport is also influenced by electrostatics and hydrodynamics, which can vary within the channel lumen. Nanoscale transport is best studied with resistive-pulse sensing, where individual molecules passing through the nanopore are registered via temporal changes of a transmembrane ion current, as used in DNA sequencing ,, and single-molecule protein sensing. , Yet, the experiments do not offer a dynamic picture of the detailed transport processes, leaving several key questions unanswered: What is the trajectory of a protein entering a channel and what is the probability that the molecule binds to a recognition site rather than simply passing the nanopore? Furthermore, does binding to a recognition site follow the strength expected from solution studies, and what is the extent and nature of nonspecific binding to a channel wall?…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Transport selectivity is usually based on size exclusion, and hence nanopore geometry and dimensions, , but also on molecular recognition via cognate receptors present inside the pore. Transport is also influenced by electrostatics and hydrodynamics, which can vary within the channel lumen. Nanoscale transport is best studied with resistive-pulse sensing, where individual molecules passing through the nanopore are registered via temporal changes of a transmembrane ion current, as used in DNA sequencing ,, and single-molecule protein sensing. , Yet, the experiments do not offer a dynamic picture of the detailed transport processes, leaving several key questions unanswered: What is the trajectory of a protein entering a channel and what is the probability that the molecule binds to a recognition site rather than simply passing the nanopore? Furthermore, does binding to a recognition site follow the strength expected from solution studies, and what is the extent and nature of nonspecific binding to a channel wall?…”
supporting
confidence: 93%
“…Transport is also influenced by electrostatics and hydrodynamics, which can vary within the channel lumen. 16 22 Nanoscale transport is best studied with resistive-pulse sensing, where individual molecules passing through the nanopore are registered via temporal changes of a transmembrane ion current, as used in DNA sequencing 10 , 11 , 13 and single-molecule protein sensing. 12 , 23 Yet, the experiments do not offer a dynamic picture of the detailed transport processes, leaving several key questions unanswered: What is the trajectory of a protein entering a channel and what is the probability that the molecule binds to a recognition site rather than simply passing the nanopore?…”
mentioning
confidence: 99%
“…30 Again, recent simulation studies have shown that electrolytes like NaCl can potentially enhance the otherwise low dielectric constant of water nanoconfined by hydrophobic walls. 58 This increase has been attributed to the randomization of the water dipoles in the presence of competing electrostatic and van der Waals interactions with the ions and confining walls, respectively. 58 Whether protons can also induce such a mechanism for water under hydrophilic confinement needs investigation.…”
Section: Discussionmentioning
confidence: 99%
“…While the enhancement of ε || in confinement is being further confirmed, , the origin of the reduced ε ⊥ is now suggested to being linked to the reduction of H-bonding between the first and second wetting layers; the latter mechanistic proposal seems surprising given that signicant reduction of ε ⊥ eff extends far away from these two layers as quantified in Figures and . Other computer simulations suggest that the presence of salts in the nanoconfined water phase reduces ε || while it increases ε ⊥ . We note that the concern about the use of the proper expressions for computing the dielectric response of water in confinement and the acknowledgement of its anisotropic character as elaborated in Section is growing .…”
mentioning
confidence: 98%